Pengaruh Media Tanam Kacang Kapri Dan Mikoriza Pada Pertumbuhan Pakcoy Tanpa Pemupukan Tambahan - Dwi Wulandari; Nanik Lutfiyah (Fakultas Pertanian, Universitas Darul Ulum, 2025)
This study aimed to determine the effectiveness of residual snow pea growing media combined with manure and mycorrhizae on the growth of bok choy without additional fertilization, supporting sustainable agriculture.The research method used was a completely randomized design (CRD) with 7 treatments and 3 replications. The treatments were as follows: P0 = 100% soil, A1D1 = 4 kg soil + 1 kg cow manure + 15 grams of mycorrhizal fertilizer. A1D2 = 3 kg soil + 2 kg cow manure + 10 grams of mycorrhizal fertilizer. A1D3 = 2 kg soil + 3 kg cow manure + 5 grams of mycorrhizal fertilizer. A2D3 = 4 kg soil + 1 kg goat manure + 15 grams of mycorrhizal fertilizer. A2D2 = 3 kg soil + 2 kg goat manure + 10 grams of mycorrhizal fertilizer. A2D3 = 2 kg soil + 3 kg cow manure + 5 grams of mycorrhizal fertilizer. Observed parameters included plant height, leaf number, fresh weight, and mycorrhizal spore density.The results showed that the combination of 1 kg of goat manure and 15 grams of mycorrhizal fertilizer (A2D1) with residual pea growing media resulted in the best growth for bok choy. In the A2D1 treatment, plant height reached 23.6 cm, with 12 leaves, and a fresh weight of 154.3 grams per plant. Meanwhile, the control treatment (P0) and the 154.3 grams of residual pea growing media alone produced the lowest growth rates.